Development of an Extractive Spectrophotometric Method for Determination of Mn (II) using 2, 4-dimethyl -3H- 1, 5 benzodiazepine - Sonali S. Patil (International Journal of Research in Chemistry and Environment (IJRCE), 2011)
A new analytical reagent 2, 4-dimethyl -3H- 1, 5 benzodiazepine (DBA) is proposed for the extraction and spectrophotometric determination of Mn (II). The Reagent was synthesized and characterized by IR, NMR, elemental analysis as well as Mass spectrometry. DBA reacts with Manganese to gives reddish yellow colored complex which can be quantitatively extracted into n-butanol at pH 7.2. The organic extract shows maximum absorption at 525nm where absorption due to similarly prepared reagent blank is negligible. The beer’s law is followed in the concentration range 1-10 μg/ml of Mn (II). The molar absorptivity and sandell’s sensitivity of Mn(II) -DBA complex is 3180 Lit mol-1cm-1 and 0.03144 mg/cm2 respectively. The proposed method is rapid, sensitive, reproducible, and accurate and has been satisfactory applied for determination and separation of Manganese (II) in commercial mixtures, pharmaceutical samples and alloys.